Immigration and Overseas Mission: The True Jesus Church's Recent Global Expansion - Iap, Joshua Sian-Chin; TSAI, Yen-Zen (Journal of Research for Christianity in China (JRCC), 2025)
The dramatic growth of Christianity in the Global South during the postcolonial era of the mid-20th century has fundamentally transformed perceptions of Western dominance and cultural imperialism in missions. These rapidly emerging Southern churches—whether pre-colonial denominations or newly independent congregations—have themselves begun overseas missionary work. Founded in Beijing in 1917, the True Jesus Church utilized overseas immigrant networks for missionary work as early as the 1920s, pioneering “reverse mission” among non-Western churches. Following the establishment of the “International United General Association,” its global expansion intensified, with non-Chinese believers steadily increasing and gradually shedding its original ethnic Chinese orientation. Discussions on religion and transnational mobility have recently become a focus in religious studies. This paper will review and discuss the True Jesus Church's transnational mobility and missionary processes within this framework, comparing its overseas expansion with that of Taiwanese or other Chinese religious groups.